The Role of Date Palm ( L) Pollen in Fertility - Mohammad Tahvilzadeh PharmD, PhD Candidate; Mannan Hajimahmoodi PharmD, PhD; Roja Rahimi PharmD, PhD (SAGE Publishing, 2016)
Date palm pollen (DPP) is the male reproductive dust of palm flowers used as dietary supplement especially as aphrodisiac and fertility enhancer in both women and men from ancient times. Although there are few clinical trials evaluating the beneficial effects of DPP in humans, various experimental studies have been conducted on the reproductive effects of DPP. Among the compounds isolated from DPP are amino acids, fatty acids, flavonoids, saponins, and estroles. The present review summarizes comprehensive information concerning the phytochemistry and pharmacological activities of DPP and its application in fertility disorders.